Predation and parasitism of naturally occurring and sentinel stink bug egg masses of Halyomorpha halys (Stål) and Nezara viridula (L.) (Hemiptera: Pentatomidae) in various southeastern habitats. Issue 2 (2nd April 2023) - Tillman, P Glynn; Grabarczyk, Erin E; Balusu, Rammohan; Kesheimer, Katelyn; Blaauw, Brett; Sial, Ashfaq; Vinson, Edgar; Cottrell, Ted E
Abstract: Stink bugs, including Halyomorpha halys (Stål) and Nezara viridula (L.), are agricultural pests that feed on fruit in a variety of crops. Monitoring predation and parasitism of stink bug egg masses furthers our understanding of potential biological control tactics. However, best practices for laboratory and field assessments of parasitism and predation of egg masses require further attention. We carried out a series of laboratory and field experiments to test whether parasitism and predation for three types of sentinel H. halys egg masses, fresh, frozen, and refrigerated, varied in agricultural commodities. In addition, we asked if predation and parasitism differed between sentinel and naturally occurring H. halys and N. viridula egg masses in soybean. In the laboratory, more H. halys eggs were parasitized by Trissolcus euschisti (Ashmead) (Hymenoptera: Scelionidae) if they were frozen or refrigerated compared to fresh eggs. Similarly, in the field, parasitism was higher for frozen egg masses than fresh. In 2018 and 2019, H. halys natural egg masses had higher parasitism and lower predation compared to sentinel egg masses in soybean. In a paired field test during 2020 and 2021, there was no difference in parasitism between H. halys natural and sentinel eggs, but much higher incidence of parasitism was detected in natural N. viridula egg masses than sentinel eggs. Collecting natural egg masses is the best methodology for field assessment of parasitism of stink bug egg masses; however, if natural egg masses are not easily available, deploying refrigerated sentinel egg masses is a good alternative.